2019
DOI: 10.14744/nci.2019.30316
|View full text |Cite
|
Sign up to set email alerts
|

Psychoactive Drug Use and Falls among Community-Dwelling Turkish Older People

Abstract: F alls are a significant common problem in older adults, reducing function and quality of life, increasing the risk for fear of falling syndrome, and causing morbidity and mortality. One-third of community-dwelling people aged over 65 years fall one or more times each year and repeated falls occur in half of them [1]. Brain trauma, hip fractures, hospitalization and death are worst outcomes of falls. Accidents are the seventh cause of deaths in older people and the majority are associated with falls [2]. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…When determining the relationship between the consumption of benzodiazepines, opioids, and tricyclic antidepressants and falls, a study showed that variables age, sex, and sensory conditions remain significantly associated, and negatively so with cannabis consumption [53]. In a recent study in Turkey, psychoactive drug treatment was found to be independently associated with the risk of falls [54]. Pratt et al (2014) discovered that increasing the number or doses of psychoactive medications was related to an increased risk of hospitalization after a fall [53].…”
Section: Discussionmentioning
confidence: 99%
“…When determining the relationship between the consumption of benzodiazepines, opioids, and tricyclic antidepressants and falls, a study showed that variables age, sex, and sensory conditions remain significantly associated, and negatively so with cannabis consumption [53]. In a recent study in Turkey, psychoactive drug treatment was found to be independently associated with the risk of falls [54]. Pratt et al (2014) discovered that increasing the number or doses of psychoactive medications was related to an increased risk of hospitalization after a fall [53].…”
Section: Discussionmentioning
confidence: 99%